Genetic polymorphisms in TNF-α as a potential biomarker for oral health-related quality of life in children - Lívia Azeredo Alves Antunes; Liz Helena Moraes Pinheiro; Thuanny Castilho; Nicolle Todoroff; Camila Duarte; Jhenyfer da Silva Tavares; Rafaela Scariot; Erika Calvano Küchler; Leonardo Santos Antunes (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: This cross-sectional study aimed to assess if genetic polymorphisms in TNF- α are associated with a negative impact on Oral Health-Related Quality of Life (OHRQoL) in children with dental caries. A total of 307 pairs of parents/caregivers and children aged two to five years were selected. The children were clinically evaluated and classified according to caries experience and severity of active caries. The Brazilian Portuguese version of the Early Childhood Oral Health Impact Scale (ECOHIS) was used to assess OHRQoL. Genotyping analysis of genetic polymorphisms in TNF- α (rs1799724, rs1799964, and rs1800629) was performed using real-time polymerase chain reaction. In the recessive model, children with the CC genotype of TNF-α (rs1799964) had a significantly high chance of poor OHRQoL in the symptom domain (pain), in both the caries experience (p = 0.045) and the high-severity active caries phenotypes (p = 0.033) (Mann-Whitney U test). It was concluded that genetic polymorphisms in TNF-α are associated with OHRQoL related to the symptom domain (pain), suggesting that TNF-α could be used as a potential biomarker for OHRQoL. Understanding the genetic aspects associated with OHRQoL will allow the early identification of patients with OHRQoL disparities and provide personalized healthcare.